Evaluation of the mechanical properties and degree of conversion of 3D printed splint material - Perea-Lowery Leila; Gibreel Mona; Vallittu Pekka K; Lassila Lippo (Elsevier, 2025)
Objective
To evaluate the effect of post-curing method, printing layer thickness, and water storage on the mechanical properties and degree of conversion of a light-curing methacrylate based resin material (IMPRIMO® LC Splint), used for the fabrication of 3D printed occlusal splints and surgical guides.
Methods
96 bar-shaped specimens were 3D printed (Asiga MAX), half of them with a layer thickness of 100 μm (Group A), and half with 50 μm (Group B). Each group was divided in three subgroups based on the post-curing method used: post-curing with light emitting diode (LED) and nitrogen gas; post-curing with only LED; and non-post-curing. Half of the specimens from each subgroup were water-stored for 30 days while the other half was dry-stored (n = 8). Flexural strength and flexural modulus were evaluated. Additional specimens were prepared and divided in the same way for surface hardness (n = 96), fracture toughness, and work of fracture (n = 96). Five specimens were selected from each subgroup for evaluating the degree of conversion (DC). Data were collected and statistically analyzed with 1-way, 2-way ANOVA, and Tukey post-hoc analysis (α = 0.05).
Results
The 2-way ANOVA showed that the post-curing method and water storage significantly affected the investigated mechanical properties (P < 0.001). The 1-way ANOVA revealed a statistically significant difference among the tested groups on the investigated properties (P < 0.001). After water storage, the 100 μm subgroup post-cured with only LED showed higher flexural strength (51 ± 9) than the 50 μm and 100 μm subgroups that were post-cured with LED in addition to nitrogen gas atmosphere (38 ± 5, 30 ± 3) (p < 0.05). The 50 μm subgroup post-cured with only LED showed the highest significant flexural modulus values (1.7 ± 0.08) (p < 0.05). However, the 50 μm subgroup post-cured with LED plus nitrogen showed significantly higher surface hardness values (p < 0.05) among the investigated groups. The non-post-cured subgroups showed the lowest values, which were significantly different from the other subgroups (p < 0.05).
Conclusion
The post-curing method, water storage, and printing layer thickness play a role in the mechanical properties of the investigated 3D Printed occlusal splints material. The combination of heat and light within the post-curing unit can enhance the mechanical properties and degree of conversion of 3D printed occlusal splints. Flexural strength and surface hardness can increase when decreasing printing layer thickness.